2013
DOI: 10.1038/srep01328
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing virulence-specific perturbations in the mitochondrial function of macrophages infected with mycobacterium tuberculosis

Abstract: To probe how the pathogen Mycobacterium tuberculosis controls host cellular death pathways, we compared mitochondrial responses in human macrophages infected either with the avirulent mycobacterial strain H37Ra, or its virulent counterpart H37Rv. Following H37Ra infection, induction of the apoptotic response was foreshadowed by the early suppression of stress-induced mitochondrial activity. In contrast, mitochondria in H37Rv-infected cells displayed robust activity with increased membrane potential and ATP syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 59 publications
6
85
0
Order By: Relevance
“…However, it is unclear which mechanisms Mtb uses to alter host cell death modes in its favor (Moraco and Kornfeld, 2014). In this study, we demonstrated that the Mtb toxin TNT damages mitochondria, a key event in the necrotic cell death of Mtb-infected macrophages (Chen et al, 2006; Duan et al, 2002; Jamwal et al, 2013). The observed mitochondrial damage is a consequence of the NAD + glycohydrolase activity of TNT and does not require a direct interaction of TNT with mitochondria, in contrast to other Mtb proteins associated with mitochondria (Cadieux et al, 2011; Sohn et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…However, it is unclear which mechanisms Mtb uses to alter host cell death modes in its favor (Moraco and Kornfeld, 2014). In this study, we demonstrated that the Mtb toxin TNT damages mitochondria, a key event in the necrotic cell death of Mtb-infected macrophages (Chen et al, 2006; Duan et al, 2002; Jamwal et al, 2013). The observed mitochondrial damage is a consequence of the NAD + glycohydrolase activity of TNT and does not require a direct interaction of TNT with mitochondria, in contrast to other Mtb proteins associated with mitochondria (Cadieux et al, 2011; Sohn et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…It is found that mitochondria in M. tuberculosis H37Rv-infected cells displayed robust activity with increased membrane potential and ATP synthesis [33]. Ultrastructural changes in the mitochondria and mitochondrial clustering are also observed in the M. tuberculosis H37Rv infected cells [33].…”
Section: Resultsmentioning
confidence: 99%
“…For example, macrophages react to some Mycobacterium tuberculosis strains by lowering the Dcm and iATP (23) and by inducing inflammasome activation and IL-1b production, ultimately promoting bacterial killing (24). Several intracellular bacteria or viruses reduce iATP levels (25).…”
Section: Discussionmentioning
confidence: 99%